Shays' Rebellion intelligence report
Intelligence report by an unknown writer concerning the Shays' Rebellion led by Daniel Shays. Discusses activities in Massachusetts and Vermont. Individuals mentioned include Daniel Shays.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Shays, Daniel, -- 1747-1825.; Shays' Rebellion, 1786-1787.; Massachusetts -- History -- 1775-1865.; Vermont -- History -- 1775-1865.